Reproducibility : principles, problems, practices, and prospects - 4 0 16; 1960- Atmanspacher, Harald.;Maasen, Sabine; 5 (Hoboken, NJ : John Wiley & Sons, 2016)
A review of the scientific method. In the scientific method, results must be capable of being reproduced to be valid.
Includes index.
Includes bibliographical references and index.
Print version record.
Keywords: 2 -- 0; 6; Methodology. -- Observation (Scientific method).;Science -- 20; 20; Electronic books. -- 2